Efektivitas Manajemen Pembiayaan Pendidikan dalam Meningkatkan Mutu Pembelajaran: Kajian Tata Kelola dan Akuntabilitas Sistem Pendidikan di Indonesia - Siti Harfihamzah Indra Naomi; Dwi Cahyaningdyah; S Martono (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effectiveness of educational financing management in improving learning quality in Indonesia from the perspectives of educational governance and accountability. The study employed a literature review method by examining relevant research articles, policy reports, and empirical evidence related to educational financing. The findings reveal a paradox between the substantial allocation of educational funding, which accounts for approximately 20% of the national state budget, and the relatively low student learning outcomes as indicated by international assessments such as PISA 2022. The structure of educational financing remains largely dominated by routine expenditures, particularly personnel salaries and allowances, limiting opportunities for investments that directly contribute to learning improvement. Furthermore, weak data integration, disparities in governance capacity across regions, and accountability mechanisms that remain predominantly administrative hinder the effective utilization of educational resources. The study concludes that improvements in learning quality are determined not only by the size of educational expenditures but also by the quality of governance, accountability systems, and policy orientations focused on learning outcomes. Therefore, a performance-based and outcome-oriented educational financing system is essential to enhance the effectiveness of educational investments and support sustainable improvements in educational quality.